Building New Bridges - Bâtir de nouveaux ponts : Sources, Methods and Interdisciplinarity - Sources, méthodes et interdisciplinarité - Sylvie Perrier (Les Presses de l'Université d'Ottawa | University of Ottawa Press, 2005)
Questions of methodology and the use of sources are fundamental to all academic disciplines. In recent years, this topic has become far more challenging as scholars are increasingly adopting an interdisciplinary approach to achieve richer and deeper analyses, particularly in the humanities and social sciences. Building New Bridges / Bâtir de nouveaux ponts is a collection of scholarly papers that deals with the first principles of source identification and their effective utilization.